Piracy among undergraduate and graduate students: influences on unauthorized book copies - Dionísio, P.; Leal, C.; Pereira, H.; Salgueiro, M. F. (Journal of Marketing Education, 2013)
The unauthorized duplication of books through photocopies and Internet downloads, especially in the case of academic books, is currently one of the most challenging problems facing the publishing industry. Photocopying has become widespread with these texts, apparently without major ethical concerns on the part of students. The purpose of this study is to investigate the factors influencing the purchase of pirated books in an academic context. To explore these factors, this study conducted a survey among Portuguese university and graduate students. The structural equation modeling framework was used to test the research hypotheses and to validate the proposed model. The outcome of this research resulted in a comprehensive integrated framework based on the effects that gender, education stage, pricing, social influence, perceived country economic conditions, and perceived risk had on the purchase behavior for pirated books. Ultimately, the outcome provided a set of recommendations in terms of marketing education.